Foreign Investment and Domestic Investment and Population Number on Economic Growth and Prosperity Level in Berau District - Purwo Hindarto; Eny Rochaida; Warsilan Warsilan (International Journal of Economics, Commerce, and Management, 2025)
The aim to be achieved through this research is analyzing and knowing the Effect of Foreign Direct Investment and Domestic Direct Investment with Total Population on Economic Growth and Welfare in Berau Regency. by using analysis path. This study is causality, which analyzes the effect of variables Independnt on the variables Dependent. The variables used are variables of Foreign Direct Investment and Domestic Direct Investment with Total Population on Economic Growth and Welfare in Berau Regency. He data used in this study are the secondary time series data from 2010 to 2017 sourced from the Provincial BPS and other sources in the Provincial Government of East Kalimantan. The data that has been collected is then analyzed quantitatively and qualitatively to provide the proposed hypothesis by using analysis path. The results show that the Foreign Direct Investment has a negatif and not significant on Economic Growht. Domestic Direct Investment has a positive and not Significant on Economic Growht. Total Population has a negatif and not significant on Economic Growth. Foreign Direct Investment has a positive and significant on Welfare. Domestic Direct Investment has a positive and not significant on Welfare. Total Population has a positive and significant on Welfare. Economic Growth has a positive and not significant on Welfare.